THE APPLICATION OF SUMMARIZING TECHNIQUE TO IMPROVE STUDENTS' WRITING ABILITY - Tiwa, Jerikho Louis; Maru, Mister Gidion; Lolowang, Imelda S. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
This study aims to determine the effectiveness of summarizing strategies in improving students’ writing ability. Students at SMA N 1 Lembean Timur continue to experience low writing proficiency, which is marked by limited English vocabulary and weak sentence construction skills. This quantitative study employed a pre-experimental design using a single-group pre-test and post-test format. Purposive sampling was used to select 20 out of 60 eleventh-grade students at SMA N 1 Lembean Timur as the research sample. The study was conducted over two weeks in May 2023. An expository writing test was used as the research instrument, requiring students to write a short expository paragraph that was evaluated based on content, organization, vocabulary, grammar, and mechanics. To determine the significance of the improvement, the data were analyzed using gain scores and a t-test. The results showed a significant improvement in students’ writing performance, with the mean pre-test score increasing from 57.50 to 74.00 in the post-test. A statistically significant difference was indicated by the significance value, which was less than 0.05 (p = 0.000 < 0.05). As a result, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. These findings demonstrate that summarizing strategies effectively enhance students’ writing abilities and should be appropriately applied in classroom instruction to improve students’ learning outcomes.